PENGARUH ABU VULKANIK ERUPSI GUNUNG SEMERU TERHADAP LAJU EROSI DAN SEDIMENTASI DI DTA (DAERAH TANGKAPAN AIR) WADUK SENGGURUH - Hendri Wijaya; Dyah Ari Wulandari (Racic : Rab Construction Research, 2025)
Historically, over the past two decades, Mount Semeru has erupted eight times, specifically in 2008, 2016, 2019, 2020, 2021, 2022, 2023, and 2024. Given Mount Semeru's frequent eruptions, studies on erosion rate predictions, sedimentation, and sediment control structures (SCS) are necessary. Research results indicate that volcanic ash significantly affects erosion rates. The erosion rate in the Sengguruh watershed, without considering the influence of volcanic ash, is 1,359,598.20 tons/year, while the rate that accounts for volcanic ash influence is 1,383,405.96 tons/year, reflecting an increase of 23,807.76 tons/year. The total sedimentation rate in the Sengguruh Reservoir, excluding the influence of volcanic ash, is 8,091,860.92 m³/year. When volcanic ash is taken into account, the total sedimentation rate increases to 8,337,270.20 m³/year, representing an increase of 245,409.29 m³/year or 2.94%. Based on the analysis, the potential sedimentation rate can be mitigated by existing SCS structures, eliminating the need for additional ones. However, since the storage capacity of the four SCS structures is nearly full, they must first be emptied. Subsequently, routine dredging should be carried out annually, with a volume of 100,000 m³/year to 150,000 m³/year.